Ativação dos músculos do membro inferior pelo procedimento de irradiação do conceito de facilitação neuromuscular proprioceptiva - Barboza, Paulo José Moté (2023)
Irradiation is the propagation of muscle contraction that starts from resistance in a specific muscle group and will spread to other synergistic muscle groups, with a functional reaction to support this activity. Physiotherapists from all over the world who use the concept of Proprioceptive Neuromuscular Facilitation (PNF) have used the irradiation procedure as a way to work the contraction of weak muscles from strong muscles in several physiotherapy patients in an empirical way, often without having electromyographic parameters that show which would be the most active patterns for the irradiation of certain muscles and whether it would be more effective to use the isotonic combination technique or just the use of concentric or isometric contraction without specific PNF technique, to irradiate. Thus, the aim of this study was to answer the following questions: Which PNF movement patterns can activate lower limb muscles and which types of contractions lead to greater recruitment of these muscles? Nineteen healthy participants aged between 18 and 40 years participated in the observational study with a cross-sectional methodological design. The participants were tested under four conditions randomly drawn: performing the pattern in an active assisted way with the hand only guiding the movement without resistance, with a concentric contraction, an isometric contraction and performing the isotonic combination technique on the four chosen PNF patterns were used a manual resistance. Surface electromyography was used in the gluteus medius, gluteus maximus, semitendinosus, adductor, rectus femoris, vastus lateralis, medial gastrocnemius and anterior tibialis muscles and a motion capture system and electromyography to identify movement and muscle activity, respectively. To compare the muscular activity between the conditions tested in the 4 patterns, an analysis of variance (MANOVA) was performed, with post-hoc Bonferroni test to identify the differences between the techniques and patterns of muscular activation. The significance level was defined as 5% (p<0.05). Results: All the patterns in the different ways that were performed showed differences in relation to the assisted active movement. For comparison of the EMG results, the multivariate MANOVA analysis showed interaction for the pattern of flexion - adduction - external rotation with elbow extension; for the anterior pelvis elevation pattern; for the flexion - abduction - internal rotation pattern with knee flexion and for the trunk extension pattern. For the comparative analysis between the patterns for each muscle activity, there was also a difference for each type of muscle activity. Conclusion: It can be concluded that the EMG response is associated with the muscular synergism of the patterns performed; in contractions with resistance and that this response will vary according to the pattern performed.